Impact of Merci Device Fracture on Clinical Outcome of Acute Ischemic Stroke after Mechanical Thrombectomy - Shi, Zhong-Song; Duckwiler, Gary R.; Loh, Yince; Liebeskind, David S.; Gonzalez, Nestor R.; Tateshima, Satoshi; Jahan, Reza; Saver, Jeffrey L.; Viñuela, Fernando (CNS neuroscience & therapeutics, 2012)
Summary Aims To investigate the frequency and predictors of Merci device fracture in patients with acute ischemic stroke treated with mechanical thrombectomy and its impact on clinical outcome. Methods We retrospectively analyzed patients with acute ischemic stroke treated by thrombectomy with the Merci Retriever and identified the presence of device fracture. The predictors of device fracture were assessed. We evaluated the impact of device fracture on hemorrhage and clinical outcome. Results Of 136 patients treated by thrombectomy, 6 (4.4%) experienced intraprocedural Merci device fracture. Internal carotid artery occlusion was associated with device fracture. The fractured X and L series Merci Retrievers were successfully ensnared in four patients. Patients with fractured devices had similar rates of successful revascularization with those without. In patients with fractured devices, no parenchymal hematomas were found, while hemorrhagic infarction and subarachnoid hemorrhage were found in three and two patients, respectively. Patients with fractured devices tended to be more dependent (modified Rankin Scale ≥ 3) at discharge, but had similar rates of in‐hospital mortality. Conclusions Merci device fracture is relatively infrequent in patients with acute ischemic stroke treated with thrombectomy. This complication may not increase the risk of parenchymal hematoma but tends to be associated with poor outcome.